Liminality in Ontario’s long-term care facilities: Private companions’ care work in the space ‘betwixt and between’ - Daly, Tamara (Compet Change, 2015)
Nursing, personal care, food and cleaning are publicly funded in Ontario’s long-term care facilities, but under-staffing usually renders all but the most basic of personal preferences superfluous. This individualization of responsibility for more personalized care has resulted in more families providing more care and opting to hire private, private companion care. With direct payment of companions becoming a growing but largely invisible facet of care, exploring companion’s roles is important. Using a six site rapid ethnographic study in long-term care facilities (i.e. observations, documents and key informant interviews (n = 167)), this paper argues that private companions occupy a liminal space between policy, family and market, and their role within institutions and in private homes may be the missing link in the care work chain in the sense that it can at once be classified as formal and informal and draws on their own and others paid and unpaid labour.